France : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that a solid economic recovery in France is under way. The economy is expected to expand by 1.2 percent in 2015, supported by an accommodative external environment. Sharply lower oil prices, a depreciated euro, low interest rates on account of quantitative easing, and the recovery in other euro area countries should underpin household consumption, lift export growth, and eventually foster a rebound in investment. The fiscal strategy, set out in the current multi-year budget law and the 2015 Stability Program, aims to bring the headline deficit below 3 percent of GDP by 2017, with a gradual adjustment based exclusively on spending containment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet